IT STRATEGIC PLAN BERDASARKAN METODE SERVICE ORIENTED ARCHITECTURE: STUDI KASUS PT TIGA NK TEKNIK LIPPO CIKARANG - Mareanus Lase; Prabowo Pudjo Widodo (Jurnal Teknik Informatika, 2015)
Abstract—PT Tiga NK Teknik requires an analysis of the strategic planning of the business field of SI and TI. This research aims to produce a form of Strategic Planning SI and TI in PT Three NK. The strategic planning and the right IT can support a company's business and development plan that will provide added value in the form of competitive advantage. This research method using Service Oriented Architecture. The results obtained from the research is creating a strategic planning framework SI and TI PT Three NK Techniques be integrated blue print. Conclusion the results of this research is to design a strategic plan framework SI and TI proposed could be implemented and used as a tool in planning the IT strategic plan and the PT Three NK Techniques in the future.